Contextualizing Ingratitude in Luke 17:12 – 18 Among the Members of Pentecostal Churches in Ika Land - Okoh, Blessing Uenosen (NIU Journal of Social Sciences; Vol 9 No 2 (2023): NIU Journal of Social Sciences, Vol. 9 No. 2, June 2023, 2023)
There is no gainsaying the fact that appreciating good deeds done is a critical attribute of a civilized person. It boosts the morale of people to do more good to others and as a result, it promotes the culture of harmony and goodwill. Expressing thanks has the power in creating a deeper and stronger relationship among people. Sadly, we live in a society that is bedeviled with Ingratitude. There is a constant display of this vice. This attitude of Ingratitude is becoming progressively evident in these last days among some members of Pentecostal Churches in Ika land of Delta North Senatorial District of Delta State. It is against this backdrop that the study aims to Contextualize the story of the nine ungrateful Lepers in Luke 17:12 – 18 among one of the Pentecostal Churches in Ika land, Ministry of Reconciliation Evangelism Explosion. Historical-critical approach was employed in the work. The study shows that Ingratitude is a state of not feeling or showing that you are grateful for something like the nine lepers that did not come to thank Jesus. The Paper further reveals the characteristics of Ingratitude which include pride, feeling of entitlement, and taking God’s blessings for granted and not being thoughtful. The findings include lack of regular emphasis on the importance of gratitude based on biblical teachings, which implies potential gap in spiritual education of gratitude among the church members. It reflects a missed opportunity to utilize gratitude as a powerful tool for sharing the Christian faith and attracting others to the church. The Study therefore recommends that biblical teaching on the unhealthy display of Ingratitude in Pentecostal Churches in Ika Land in particular and the Christian communities in general should be deemphasized. Keywords: Ingratitude, Pentecostal, Churches, Lepers, Contextualize